Deskripsi Pemanfaatan Media Pembelajaran di Sekolah Dasar Negeri 26 Sungai Pinyuh - Indaswari, Indaswari (Jurnal Multidisiplin Indonesia, 2024)
This research aims to describe how learning media is used at SD Negeri 26 Sungai Pinyuh. This research uses descriptive qualitative methods with instruments in the form of observation sheets and interview guides. The research data source involved class I, II, and III teachers. Based on the research results, it was found that teachers at SD Negeri 26 Sungai Pinyuh used visual media in every meeting, with an average percentage of 100% in all classes. Teachers make good use of learning media, starting with preparation which includes selecting the type of media that suits the learning objectives, as well as considering various aspects related to its use. Apart from that, teachers also plan the steps needed so that the use of this media can help achieve learning objectives.